Pembuatan Aplikasi Pelaporan dan Antisipasi Kejadian Kejahatan Berbasis Android - Christian Chandra Wijaya; Henry Novianus Palit; Kristo Radion Purba (Jurnal Infra, 2018)
Countries in the world certainly face crime problems, including Indonesia. With the high level of crime in Indonesia, we cannot fully rely on the police.Based on a survey by a marketing firm called Waiwai Marketing, Indonesia is noted as a country in the Southeast Asia with most Android users. The total is 41 million users. This motivates the development of an Android-based application for reporting and anticipating crime incidents. The application is created using Java, HTML, PHP, JavaScript, MySQL database, and Bootstrap.The application gives icons on the map according to location of incident and crime category, gives notifications to users within a certain radius from crime location, allows users to comment on crime events that have been uploaded to the system, and allows the system admin to combine the same news reported by users.